2010
DOI: 10.1002/hec.1468
|View full text |Cite
|
Sign up to set email alerts
|

Gender gap in parents' financing strategy for hospitalization of their children: evidence from India

Abstract: The 'missing women' dilemma in India has sparked great interest in investigating gender discrimination in the provision of health care in the country. No studies, however, have directly examined discrimination in health-care financing strategies in the case of severe illness of sons versus daughters. In this paper, we hypothesize that households who face tight budget constraints are more likely to spend their meager resources on hospitalization of boys rather than girls. We use the 60th round of the Indian Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 36 publications
6
50
0
1
Order By: Relevance
“…This is in contrast to a large-scale study in India that demonstrated a higher rate of hospitalization for boys than girls, with the gender difference being even more pronounced when money to pay for services had to be borrowed or assets had to be sold. 61 To date, there have been no studies of out-of-pocket expenditures incurred by parents of children undergoing cataract surgery, which, given the relatively high cost of providing cataract services for children, 62,63 are likely to be considerable in settings where fees for cataract surgery are higher than the fees adults are charged for cataract surgery. The overall explanation for the lower access to surgery by girls with bilateral cataract is likely to reflect a complex interplay of social, economic, and attitudinal factors, with poverty, low levels of maternal education, and cultural norms being key factors.…”
Section: Discussionmentioning
confidence: 98%
“…This is in contrast to a large-scale study in India that demonstrated a higher rate of hospitalization for boys than girls, with the gender difference being even more pronounced when money to pay for services had to be borrowed or assets had to be sold. 61 To date, there have been no studies of out-of-pocket expenditures incurred by parents of children undergoing cataract surgery, which, given the relatively high cost of providing cataract services for children, 62,63 are likely to be considerable in settings where fees for cataract surgery are higher than the fees adults are charged for cataract surgery. The overall explanation for the lower access to surgery by girls with bilateral cataract is likely to reflect a complex interplay of social, economic, and attitudinal factors, with poverty, low levels of maternal education, and cultural norms being key factors.…”
Section: Discussionmentioning
confidence: 98%
“…A conscious gender bias in favour of boys with regard to nutrition and care is one possible mechanism. There is substantial evidence for the existence of such a bias in southern Asia, 5,10,31 but evidence is mixed for sub-Saharan Africa. 13,[32][33][34] More detailed analyses into the causes of the observed gender differences are needed before strong conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Countries with entrenched cultural preferences for boys over girls ('son preference') include China, India, Pakistan, Egypt, Bangladesh, Iran, Afghanistan, Syria, Algeria, Turkey and Tunisia. There is an indirect pathway from son preference to poorer health outcomes though reduced access to food and nutrition, education, employment and health care, which leads on to poorer nutrition, as part of a relative neglect of girl children, which cumulatively leads to poorer health outcomes (Asfaw et al 2010;Jayachandran andKuziemko, 2011, Osmani andSen, 2003). But a more direct pathway to higher death rates and lower survival chances has also been postulated: through mechanisms such as infanticide of girl babies, and -in recent decades when technologies have developed -the practice of sex selective abortion (Banister, 2004;Klasen and Wink, 2003).…”
Section: Gender Discrimination and The Low Status Of Womenmentioning
confidence: 99%